Where are we short and who are we short of? A review of the human resources for health in South Africa - Gavin George; Timothy Quinlan; Candice Reardon; Jean-François Aguilera (AOSIS, 2012)
This review showed that thinking about the shortage of health care personnel merely in terms of insufficient numbers prevents sound strategic interventions to solve the country's human resources for health (HRH) problem. It revealed that the numbers shortage was one facet of a broader problem that included the mal distribution of HRH, production of the wrong skills in the nursing care, the attrition of staff from the public health services and, contextually, the ever-changing demands on the health services. The challenge in South Africa was furthermore to train and retain health care personnel with skills and expertise that are commensurate with the changing demands on the public health services. Uit hierdie oorsig het dit duidelik geblyk dat die tekort van gesondheidsorgpersoneel slegs in terme van ontoereikende getalle val en 'n omvattende strategiese ingryping om die land se menslike gesondheidshulpbron krisis op te los, belemmer. Dit het aangedui dat die getalletekort  maar slegs een fasset van 'n groter probleem uitmaak, wat onder andere die volgende insluit: die oneweredige verspeiding van menslike gesondheidshulpbronne, 'n fokus op ontoepaslike vaardighede in die opleiding van verpleegpersoneel, die behoud van personeel in die openbare gesondheidsektor, asook die konstant-veranderlike eise van die gesondheidsdienste. Verder was die uitdaging in Suid Afrika die opleiding en behoud van gesondheidsorgpersoneel met kennis en vaardighede wat tred hou met die veranderlike eise van die openbare gesondheidsdienste.